Food technological potentials of CO2 gas hydrate technology for the concentration of selected juices*. Issue 2 (3rd April 2019) - Seidl, P.; Loekman, S.; Sardogan, M.; Voigt, E.; Claßen, T.; Ha, J.; Luzi, G.; Sevenich, R.; Agudo, J. Rodriguez; Rauh, C.; Delgado, A.
ABSTRACT: CO2 gas hydrate technology seems to be a gentle way to concentrate juices, especially comparing to evaporation processes which achieve high levels of concentration and is furthermore energetically favorable in contrast to freeze concentration processes. CO2 can form gas hydrates at around 30–80 bar and 274–283 K. For evaluating this new technology, it is not only important to know the phase equilibrium lines of commercial juices like apple and orange juices but also how the application of e.g. a bubble column affects the gas hydrate formation and separation from the concentrated product. In order to support the experimental outcome, numerical modeling seems suitable to understand the physical background of this novel concentration technology. This includes the simulation of temperature, velocity, pressure and concentration fields using finite volume technique. All three work packages combined will lead to a better understanding of the behavior of gas hydrate technology used to concentrate liquid food.